2017
DOI: 10.14444/4009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perioperative steroids on dysphagia after anterior cervical spine surgery: A systematic review

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Many spine surgeons worry that steroids negatively impact bony fusion rates and are reluctant to use steroids. Our results demonstrated that there was no difference in fusion rates at 1-year follow-up between the steroids group and control group, which were consistent with those of prior studies of perioperative steroids ( 18 , 22 , 29 , 39 , 41 ). Nevertheless, the steroids may hinder early fusion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Many spine surgeons worry that steroids negatively impact bony fusion rates and are reluctant to use steroids. Our results demonstrated that there was no difference in fusion rates at 1-year follow-up between the steroids group and control group, which were consistent with those of prior studies of perioperative steroids ( 18 , 22 , 29 , 39 , 41 ). Nevertheless, the steroids may hinder early fusion.…”
Section: Discussionsupporting
confidence: 92%
“…Cheng et al ( 40 ) reviewed 3 RCTs and 2 retrospective cohort studies, and concluded that local corticosteroid application could reduce the incidence and severity of dysphagia following ACDF. Adenikinju et al ( 41 ) reviewed 5 RCTs and 2 retrospective cohort studies, and concluded that patients received systemic and local steroids benefit from reductions in rate and severity of dysphagia postoperatively. However, our finding is a novelty because we performed a qualitative synthesis of RCTs and discuss dysphagia without the differences in time points.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, a lesser rate of dysphagia in the early post-operative period would provide a proof of concept that minimally invasive tubular approaches, in fact, reduce soft-tissue trauma and their related complications. Worldwide rates of dysphagia are reported to be around 8.5 (5.7-11.3%, 95% confidence interval) as reported by Shriver et al in their meta-analysis of 14 papers evaluating post-operative dysphagia after ACDF 28 , among them, the greatest rate of dysphagia (39%) was reported by Keppler on a cohort study with mean follow-up of 1.5 months 1 , becoming also the paper with the shortest follow-up, which translates in a high dysphagia rate in the early post-operative period, providing evidence of the important role of soft-tissue trauma in the genesis of dysphagia, a fact that can help understand why steroids have proofed effective in reducing early post-operative dysphagia [32][33][34] driven by their known anti-inflammatory effects. Conversely, our present series results report a 9% rate of dysphagia by 1-month follow-up, presenting a 9% dysphagia rate in day-1 post-operative that fully recovered by the end of follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…Postoperative dysphagia may be due to endotracheal intubation, retraction of the oesophagus, and soft tissue inflammation. Preoperative systemic steroid treatment leads to a reduction of dysphagia severity, with no increase in infectious complications [15]. During this period, a liquid diet and gargling with lukewarm water are advised.…”
Section: Discussionmentioning
confidence: 99%